Priority areas and integrated actions for the conservation of Amazonian turtle populations historically over-exploited by humans - Brega Gamba, Fábio; Falcon, Guth Berger; Soledad Simoncini, Melina; Antônio Machado Balestra, Rafael; Malvasio, Adriana (Ethnobiology and Conservation, 2022)
The definition of priority areas for conservation and integrated management actions are essential for the effective maintenance and recovery of natural populations, especially for species overexploited by humans. Amazonian chelonians are a food resource historically used by people, resulting in the decline of species populations and worsening the risk of local extinctions. In this paper, we establish priority areas and define integrated conservation actions for populations of three Amazonian chelonians most threatened by human consumption in Brazil (Podocnemis expansa, P. unifilis and P. sextuberculata). To do so, we used 15 prioritization criteria (ecological, logistical and socioeconomic) estimated with 30 years monitoring data in 15 areas by the Amazon Chelonian Program (in portugues Projeto Quelonios da Amazonia, PQA). Each criterion presented four levels of priority with scores increasing according to the relevance for conservation of chelonian populations. The sum of the scores obtained in each area of the PQA allowed a ranking and four categories of importance for conservation to be defined. We also analyzed the similarity of scores among areas of the PQA and among the prioritization criteria to evaluate the application of integrated conservation action strategies. The areas of PQA were classified as Extremely Important for Conservation (Rebio Trombetas River, Middle Xingu River, Middle Araguaia River, Upper Guaporé River), Very Highly Important for Conservation (Middle Purus River, Middle Juruá River, Crixás-Açu River Mouth, Sub-middle Tapajós River); Highly Important for Conservation (Sub-Middle Araguaia River, Amazonas River Mouth, Middle Mortes River); and Important for Conservation (Middle Guaporé River, Lower Branco River, Flechal River, Afuá River). The prioritization and similarity analyses can support the development of a national integrated plan of conservation actions to reduce the overexploitation of Amazon chelonian populations, according to the ecological, logistical and socioeconomic needs of each PQA area.